Interaction between mesenchymal stem cells and Ti-30Ta alloy after surface treatment - Capellato, Patricia; Escada, Ana L. A.; Popat, Ketul C.; Claro, Ana P. R. Alves (Wiley, 2013)
In this study, in vitro cytocompatibility was investigated in the Ti-30Ta alloy after two kinds of surfaces treatments: alkaline and biomimetic treatment. Each condition was evaluated by scanning electron microscopy/energy-dispersive X-ray spectroscopy. Cellular adhesion, viability, protein expression, morphology, and differentiation were evaluated with Bone marrow stromal cells (MSCs) to investigate the short and long-term cellular response by fluorescence microscope imaging and colorimetric assays techniques. Two treatments exhibited similar results with respect to total protein content and enzyme activity as compared with alloy without treatment. However, it was observed improved of the biomineralization, bone matrix formation, enzyme activity, and MSCs functionality after biomimetic treatment. These results indicate that the biomimetic surface treatment has a high potential for enhanced osseointegration. © 2013 Wiley Periodicals, Inc.
Keywords: Alkali treatment; Biocompatibility; Biomimetic treatment; Bone marrow stromal cells; Ti-30Ta alloy